Determining the Source of the Explosive Sound Heard in Hokkaido, Japan, on 26 April 2021. Issue 12 (4th December 2021) - Yamada, Masumi
Abstract: An explosive sound was heard over a wide area of Sapporo city, Hokkaido, Japan, on 26 April 2021. It was accompanied by minor shaking and was considered likely to be a sonic boom produced by a fireball. However, no luminous phenomenon was observed. We analyzed seismic data to identify the source of the sonic boom, and estimated the trajectory of the object from the associated signal arrival times. The source was located ∼100 km off the west coast of Hokkaido at an altitude of 50 km. The elevation angle was greater than 66° and the estimated velocity was higher than that of a fighter plane. Although the luminous phenomenon was not observed, the trajectory model suggested that the source of the sonic boom was not an aircraft and most likely a fireball. We compared trajectory models estimated from optical and seismic observations for past sonic boom events, and they were found to be in good agreement. Although our trajectory model is simplified and assumes that sound and the fireball have a constant speed, the model is highly accurate. The results show that seismic data can be used to estimate the trajectory of objects producing sonic booms, even when visual observations are unavailable. Plain Language Summary: An unexplained explosive sound was heard around Sapporo city, Hokkaido, Japan at 20:00 JST on 26 April 2021. The sound and the resulting minor tremors were widely felt throughout the densely populated city. To determine the source of the explosive sound, we analyzed the data obtained by seismometers and found that the signals of the tremors had been recorded. The explosive sound represented a sonic boom, which is a loud sound generated by an object traveling faster than the speed of sound. Based on the arrival pattern of the signal, we estimated the location and moving direction associated with the source of this sound. The source was located about 100 km off the west coast of Hokkaido and the estimated velocity was higher than that of a fighter plane. Although no luminous phenomenon was observed, we believe the sonic boom was generated by a fireball. Key Points: We analyzed seismic data to identify the source of an explosive sound heard in Sapporo city, Hokkaido, Japan, on 26 April 2021 A trajectory model was established, and the source was identified as an object producing a sonic boom that was most likely a fireball Seismic data can be used to estimate the trajectory of objects producing sonic booms, even those not visually observed